Unsafe abortions in Sri Lanka -facts and risk profile - N Thalagala (College of Community Physicians of Sri Lanka, 2012)
Introduction Unsafe abortions frequently endanger the lives of Asian women. Research on diverse aspects of this important public health problem is considered an urgent need. Methodology Six hundred and sixty five women with a history of an unsafe abortion were compared with a control group of pregnant women who had never undergone an abortion. The processes of abortions were summarized. The two groups were compared to identify factors that may raise the risk of resorting to an unsafe abortion. The significance and the strength of respective associations were determined using regression analysis. Results Unmet needs in family planning accounted for 73% of unsafe abortions. Over 84% of women knew undergoing an unsafe abortion could lead to serious life threatening conditions. Seventy five percent knew that abortion was illegal. Nearly 92% of unsafe abortions were performed surgically, mostly by unqualified personnel. Risk factors identified included; economic hardships, lower educational standards, poor religious devotedness, perceived burden of child rearing, poor lower family and social support, strained marital relationship, peers influence in reproductive decisions and having an important life goal that is likely to be obstructed by having a pregnancy. Conclusion Awareness on potential complications or legal restrictions did not prevent women from resorting to unsafe abortion. The quality of services received by abortion seekers was very poor. Ensuring access to family planning alone may result in a significant reduction in the burden of unsafe abortion. DOI: http://dx.doi.org/10.4038/jccpsl.v15i1.4934 Journal of the College of Community Physicians of Sri Lanka Vol.15(1) May 2010 1-12